2019
DOI: 10.31080/asnh.2019.03.0545
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spray Drying Conditions on the Physical and Bioactive Properties of New Zealand Tamarillo (Solanum betaceum) Powder

Abstract: This research investigates the effect of spray drying conditions on the chemical and physical characteristics of tamarillo powders encapsulated with either maltodextrin (MD), gum arabic (GA), or a combination of both carriers. Tamarillo puree was spray dried at different inlet temperatures from 100°C to 140°C. The highest yield was at 50.60% obtained at an inlet temperature of 120°C.Colour, water activity and solubility of tamarillo powder were significantly affected by drying inlet temperature and carriers us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…From Table 1, it can be seen that variances of inlet temperatures did not affect the solubility and wettability of powders obtained. Similar result was also reported by Al Mubarak et al (2019), that the inlet spray drying temperature did not have a major effect on the water solubility index, bulk density, and hygroscopicity of Tamarillo powder. Meanwhile, the sample with 30% Brix were had the longest wetting time, ranged from 3500 -4500 s. This result is similar to that in coconut powder reported by A-Sun et al (2016), who revealed that the higher solid content would reduce the porous structure of powder.…”
Section: Results and Discussion Physical Propertiessupporting
confidence: 90%
“…From Table 1, it can be seen that variances of inlet temperatures did not affect the solubility and wettability of powders obtained. Similar result was also reported by Al Mubarak et al (2019), that the inlet spray drying temperature did not have a major effect on the water solubility index, bulk density, and hygroscopicity of Tamarillo powder. Meanwhile, the sample with 30% Brix were had the longest wetting time, ranged from 3500 -4500 s. This result is similar to that in coconut powder reported by A-Sun et al (2016), who revealed that the higher solid content would reduce the porous structure of powder.…”
Section: Results and Discussion Physical Propertiessupporting
confidence: 90%
“…Tamarillo is a perishable fruit, and the pulp is subjected to convective drying and spray drying techniques (García et al, 2018) for preservation and use. Literature reports mention the use of spray drying techniques for tamarillo (Al Mubarak et al, 2019; Ramakrishnan et al, 2018). However, spray drying technique has limited suitability for pulp and viscous juices (de Cól et al, 2021).…”
Section: Introductionmentioning
confidence: 99%